Proposed marketing strategy for PT. Harmony land group in facing off uncertainty period - Muhammad, Fithor (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
In the fourth year of PT. Harmony Land Group growth, an unexpected big disaster is coming, Pandemic Covid 19. The property business is greatly affected, people are afraid to leave house, even less to buy a house. After struggling to survive in a pandemic situation without firing any employees, Harmony Land started looking for the next opportunity. One big issue that Harmony Land wants to solve is increasing the act per ask at A5 costumer journey. This research is to analyst internal and external business condition of PT Harmony Land Group; To understanding customers’ need by doing customer behavior research. To propose strategy to increase conversion rate act per ask. This research employed quantitative and qualitative method or mix method. In addition, the researcher also applied AFI framework. Based on the result it can be concluded that housing Market is high competition, but because of the demand always grow while supplier is cannot be renewable make housing business is very prospective. Pandemic Covid make customer that should be buy house in 2020 until 2022 pending their purchase, so after pandemic end, there will be boom demand, because customer which pending their purchase will buy and new customer still will buy.